Phage‐assisted, active site‐directed ligand evolution of a potent and selective histone deacetylase 8 inhibitor. (28th November 2022) - Morse, Jared S.; Sheng, Yan J.; Hampton, Joshua Trae; Sylvain, Lauralee D.; Das, Sukant; Alugubelli, Yugendar R.; Chen, Peng‐Hsun Chase; Yang, Kai S.; Xu, Shiqing; Fierke, Carol A.; Liu, Wenshe Ray
Abstract: Phage‐assisted, active site‐directed ligand evolution (PADLE) is a recently developed technique that uses an amber codon‐encoded noncanonical amino acid (ncAA) as an anchor to direct phage‐displayed peptides to a target for an enhanced ligand identification process. 2‐Amino‐8‐oxodecanoic acid (Aoda) is a ketone‐containing ncAA residue in the macrocyclic peptide natural product apicidin that is a pan‐inhibitor of Zn 2+ ‐dependent histone deacetylases (HDACs). Its ketone serves as an anchoring point to coordinate the catalytic zinc ion in HDACs. Using a previously evolved N 𝜀 ‐ acetyl‐lysyl‐tRNA synthetase in combination with tRNA Pyl, we showed that Aoda was efficiently incorporated into proteins in Escherichia coli by amber suppression. By propagating an amber codon‐obligate phagemid library in E. coli encoding Aoda, we generated an Aoda‐containing phage‐displayed peptide library. Using this library to conduct PADLE against HDAC8 revealed a 7‐mer peptide GH8P01F1 with Aoda‐flanking amino acid residues that matched existing peptide sequences in identified HDAC8 substrates. Switching Aoda in GH8P01F1 to a more Zn 2+ ‐chelating ncAA S ‐2‐amino‐8‐hydroxyamino‐8‐oxooctanoic acid (Asuha) led to an extremely potent compound GH8HA01, which has an HDAC8‐inhibition K i value of 0.67 nM. GH8HA01 and its 5‐mer truncation analogue Ac‐GH8HA01 Δ 1 Δ 7 that has an HDAC8‐inhibition K i value of 0.31 nM are two of the most potent HDAC8 inhibitors that have been developed. Furthermore, both are highly selective against HDAC8 compared with other HDACs tested, demonstrating the great potential of using PADLE to identify highly potent and selective ligands for targets with conserved active sites among homologues.